ECOLOGICAL-VALEOLOGICAL CULTURE IN THE "MAN-NATURE-SOCIETY" SYSTEM (Web of Teachers: Inderscience Research, 2024)
In the world, the ecological-valeological culture of students is the formation of the ecological worldview of a person who is ready to live in conditions of social danger, to overcome the movement capable of creating effective models, to control natural processes, to the educational process through specific factors that cause harm, nature and human health. applied. The article discusses the need for systematic work on the development of students' self-image skills, development of curiosity, ecological and valeological knowledge, and the formation of ecological awareness, thinking and worldview.